The effect of a synthetic-grass sport surface on physiology and perception during intermittent exercise in hot conditions - Singh, G.; Bennett, K. J. M.; McGuigan, H.; Goddard, S. G.; Stevens, C. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose The current study aimed to determine the effect of a synthetic-grass sport surface on core body temperature, skin temperature, heart rate, thermal sensation, thermal comfort, and rating of perceived exertion (RPE) during intermittent exercise in hot conditions.